Need for cognitive closure, tolerance for ambiguity, and perfectionism in medical school applicants - Gärtner, Julia (BMC Med Educ, 2020)
BACKGROUND: Physicians have to deal with uncertainty on a daily basis, which requires high tolerance for ambiguity. When medical decisions have to be made in ambiguous situations, low levels of need for cognitive closure and high levels of adaptive perfectionism are beneficial. It might be useful to measure such personality traits during medical school selection processes. In our study, we explored the expression of need for cognitive closure, tolerance for ambiguity, and perfectionism in medical school applicants who participated in a multiple mini-interview selection process with respect to the final decision of admission or rejection. METHODS: After participating in the multiple mini-interview procedure (HAM-Int) at Hamburg Medical School in August 2019, 189 medical school applicants filled out a questionnaire including the Multidimensional Perfectionism Scale by Hewitt and Flett (MPS-H), the Multidimensional Perfectionism Scale by Frost (MPS-F), the Tolerance for Ambiguity Scale (TAS), the 16-Need for Cognitive Closure Scale (16-NCCS), and sociodemographic data. After the final admission decision, the scores of need for cognitive closure, tolerance for ambiguity, and perfectionism of admitted and rejected applicants were compared. We also assessed the predictive power of need for cognitive closure and age for the admission decision in a binary logistic regression model. RESULTS: Compared to the admitted applicants, the rejected applicants showed a significantly higher need for cognitive closure (p = .009). A high need for cognitive closure correlated significantly positively with maladaptive perfectionism (p < .001) and significantly negatively with tolerance for ambiguity (p < .001). Low need for cognitive closure and older age were associated with a positive admission decision. CONCLUSIONS: Regarding the personality traits need for cognitive closure, tolerance for ambiguity, and perfectionism we identified interesting differences and correlations of relevance for physicians’ daily work in medical school applicants who were admitted or rejected after participating in a multiple mini-interview selection procedure. Further studies are needed to investigate these characteristics and their development longitudinally in medical students and to correlate them with students’ medical performance.